Judicial accountability: asset disclosures and beyond - Bhushan, Prashant (2009)
Public pressure, the principled position taken by certain judges and one ruling by the Delhi High Court have compelled public disclosure of assets by judges. But this is certainly not the end of the serious problem of a lack of judicial accountability. The main issue is the absence of an independent credible institution which could entertain complaints against judges, investigate them and take action against errant members of the bench. - Reproduced.
Keywords: Accountability; Judiciary